1999
DOI: 10.1038/sj.bjc.6690112
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of the IGF-1 receptor in a tamoxifen-resistant human breast cancer cell line

Abstract: SummaryThe relationship between oestrogen (E 2 ) and insulin-like growth factor-one (IGF-1) was examined in both tamoxifen-sensitive (MCF 7/5-21) and tamoxifen-resistant (MCF 7/5-23) subclones of the MCF 7 cell line. Both subclones were grown in defined, serum-free (SF) medium over a period of 7 days with the addition of E 2 or IGF-1 or a combination of both agents. Growth of both MCF 7/5-21 and 7/5-23 cells was stimulated (245% and 350%, respectively) by E 2 . However, only the growth of MCF 7/5-23 cells was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
48
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 39 publications
1
48
1
Order By: Relevance
“…6). Although IGFR levels have been reported to be dependent on estrogen (9,14), this has not been a universal finding in all reports (41). Although results presented here suggest that discrepancies may be explained by lack of consideration to cell density in assays, another explanation could lie with the different culture conditions used.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…6). Although IGFR levels have been reported to be dependent on estrogen (9,14), this has not been a universal finding in all reports (41). Although results presented here suggest that discrepancies may be explained by lack of consideration to cell density in assays, another explanation could lie with the different culture conditions used.…”
Section: Discussioncontrasting
confidence: 51%
“…However, upon long term removal of estrogen from the culture medium, the cells gradually adapt, developing an ability to grow without estrogen until they can eventually grow at the same rate as they had done previously only in the presence of estrogen (38 -40). Similar adaptive processes enable the cells to escape from growth inhibition imposed by the anti-estrogens tamoxifen (41) and ICI 182,780 (42) or by retinoic acid (43). The molecular basis for this growth adaptation remains unknown, but recent work has shown that development of estrogen hypersensitivity resulting from up-regulation of ER and increased estrogen-regulated gene expression may be involved (44).…”
mentioning
confidence: 99%
“…Also, IGF-IR is frequently overexpressed in breast cancer (Surmacz, 2000) with tyrosine kinase activity of IGF-IR increased as much as 40-fold in tumor cells compared with normal breast tissue (Resnik et al, 1998). Upregulation of IGF-IR signaling has also been implicated in mediating resistance of breast cancer cells to chemotherapeutic agents, radiation, and targeted therapies such as Tamoxifen (Parisot et al, 1999) and Herceptin (Lu et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…While controversial, additional model systems tentatively implicate IGF-IR signalling in tamoxifen resistance. Growth of the tamoxifen-resistant MCF-7/ 5-23 cell line was significantly inhibited by the IGF-1R antibody aIR-3 (Parisot et al 1999), while further acquired tamoxifen-resistant models have been described where proliferation is dependent on IGF signalling (Wiseman et al 1993). There thus appears to be emerging evidence of a role for IGF-1R in acquired tamoxifen-resistant as well as -responsive cells.…”
Section: Introductionmentioning
confidence: 99%